ANZIAM Mathsport Proceedings (ANZIAM MathSport, 2016)
Full Proceedings for the First Mathematics and Computers in Sport Conference (1MCS), Bond University, 1992; Full Proceedings for the Second Mathematics and Computers in Sport Conference (2MCS), Bond University, 1994; Full Proceedings for the Third Mathematics and Computers in Sport Conference (3MCS), Bond University, 1996; Full Proceedings for the Fourth Mathematics and Computers in Sport Conference (4MCS), Bond University, 1998; Full Proceedings for the Fifth Mathematics and Computers in Sport Conference (5MCS), University of Technology, Sydney, 2000; Full Proceedings for the Sixth Mathematics and Computers in Sport Conference (6MCS), Bond University, 2002; Full Proceedings for the Seventh Mathematics and Computers in Sport Conference (7MCS), Massey University, New Zealand, 2004; Full Proceedings for the Eighth Mathematics and Computers in Sport Conference (8MCS), Greenmount Resort, Coolangatta, Qld., 2006; Full Proceedings for the Ninth Mathematics and Computers in Sport Conference (9MCS), Twin Towns Resort, Tweed Heads, NSW, 2008; Full Proceedings for the Tenth Mathematics and Computers in Sport Conference (10MCS), Crowne Plaza, Darwin, NT, 2010; Full Proceedings for the Eleventh Mathematics and Computers in Sport Conference (11MCS), Melbourne, Australia, 2012; Full Proceedings for the Twelfth Mathematics and Computers in Sport Conference (12MCS), Darwin, Australia, 2014; Full Proceedings for the Thirteenth Mathematics and Computers in Sport Conference (13MCS), Melbourne, Australia, 2016.